Development of mental health first-aid guidelines for suicide risk: a Delphi expert consensus study in Argentina and Chile - Encina Zúñiga, Esteban (2023)
Background: Suicide continues to pose a significant global public health challenge and ranks as one of the leading causes of death worldwide. Given the prevalence of suicide risk in the community, there is a significant likelihood of encountering individuals who may be experiencing suicidal thoughts or plans, creating an opening for non-health professionals to offer support. This study aims to culturally adapt the original Australian Mental Health First Aid Guidelines for suicide risk to the Chilean and Argentine context. Methods: A two-round Delphi expert consensus study was conducted involving two panels, one comprising individuals with personal experience in suicide thoughts/attempts or caregiving for those with such experiences (n = 18), and the other consisting of professionals specialized in suicide assessment and support for individuals at risk (n = 25). They rated a total of 179 items mainly derived from guidelines developed by Australian experts and translated into Spanish (168), and new items included by the research team (11). The panel members were requested to assess each item utilizing a five-point Likert scale. During the second round, items that received moderate approval in the initial round were re-evaluated, and new items suggested by the local experts in the first round were also subjected to evaluation in the next round. Inclusion in the final guidelines required an 80% endorsement as “essential” or “important” from both panels. Results: Consensus of approval was reached for 189 statements. Among these, 139 statements were derived from the English-language guidelines, while 50 locally generated statements were accepted during the second round. A significant difference from the original guideline was identified concerning the local experts’ reluctance to discuss actions collaboratively with adolescents. Furthermore, the local experts proposed the inclusion of an entirely new section addressing suicide risk in older individuals, particularly focusing on suicide methods and warning signs. Conclusions: A Delphi expert consensus study was conducted to culturally adapt mental health first aid guidelines for assessing suicide risk in Chile and Argentina. This study involved professionals and individuals with lived experience. While many items were endorsed, some related to inquiring about suicide risk and autonomy, particularly for adolescents, were not. An additional section for older individuals was introduced. Future research should explore the implementation and impact of these adapted guidelines in training courses. This is vital for enhancing mental health support and implementing effective suicide prevention strategies in Chile and Argentina.